Analysis of The Influence of Religiusity, Legal Awareness, and Education on Tax Reduction Zakat with Profit Quality as Moderation - Muhammad Saddam; Syahril Djaddang; Darmansyah Darmansyah; Herman Rustandi (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
This study examines the influence of religiosity, legal awareness, and education on tax reduction zakat, with profit quality as a moderator. The data was collected from 70 respondents, and the statistical analysis was conducted using multiple regression analysis and moderated regression analysis. The results show that religiosity, legal awareness, and education have a significant positive effect on tax reduction zakat. Furthermore, the study finds that profit quality moderates the relationship between religiosity and tax reduction zakat. However, the study finds no significant moderation effect for legal awareness and education on the relationship between tax reduction zakat and profit quality. This study provides insights into the factors that influence tax reduction zakat and the role of profit quality in moderating the relationship between religiosity and tax reduction zakat. The findings may be useful for policymakers, tax authorities, and companies in developing strategies to improve tax compliance and zakat payment.